First pregnancy in China after ovarian tissue transplantation to prevent premature ovarian insufficiency. (2nd November 2021) - Ruan, X.; Du, J.; Lu, D.; Duan, W.; Jin, F.; Kong, W.; Wu, Y.; Dai, Y.; Yan, S.; Yin, C.; Li, Y.; Cheng, J.; et al.
Abstract: Objective: This article reports the first case of pregnancy after frozen–thawed ovarian tissue transplantation to prevent iatrogenic premature ovarian insufficiency in China. Methods: Ovarian tissue cryopreservation was performed in a patient with myelodysplastic syndrome (MDS) before multi-agent chemotherapy and hematopoietic stem cell transplantation. Two years later, she showed complete remission from MDS, and six frozen–thawed ovarian tissue strips were transplanted into the peritoneal pocket. Results: The patient's ovarian activity was restored 3 months after transplantation, and pregnancy occurred spontaneously 27 months after grafting. Until now, the pregnancy has progressed for 30 weeks, and the repeated ultrasound showed normal fetal development. Conclusion: This is the first pregnancy resulting from ovarian tissue cryopreservation and transplantation in China.